2011
DOI: 10.1136/adc.2011.211318
|View full text |Cite
|
Sign up to set email alerts
|

Growth in the neonatal period after repeat courses of antenatal corticosteroids: data from the ACTORDS randomised trial

Abstract: Babies exposed to weekly doses of repeat antenatal corticosteroids demonstrate postnatal growth acceleration 3-5 weeks after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…There was a trend towards an incremental decrease in birth weight, length and head circumference for each additional course of antenatal corticosteroids. According to the results of the ACTORDS (Antenatal Collaborative Trial of Repeat Doses of Prenatal Steroids) trial, infants exposed to weekly doses of repeat antenatal corticosteroids presented postnatal growth acceleration 3–5 weeks after birth, which is similar to the catch-up growth observed in intrauterine growth restricted infants [46 ▪ ]. Compared with a single course of antenatal glucocorticoids, exposure to repeated doses of antenatal betamethasone was not associated with adverse effects on lung function or altered bone mass in early school-age children [47,48].…”
Section: Multiple Steroid Dosesmentioning
confidence: 90%
“…There was a trend towards an incremental decrease in birth weight, length and head circumference for each additional course of antenatal corticosteroids. According to the results of the ACTORDS (Antenatal Collaborative Trial of Repeat Doses of Prenatal Steroids) trial, infants exposed to weekly doses of repeat antenatal corticosteroids presented postnatal growth acceleration 3–5 weeks after birth, which is similar to the catch-up growth observed in intrauterine growth restricted infants [46 ▪ ]. Compared with a single course of antenatal glucocorticoids, exposure to repeated doses of antenatal betamethasone was not associated with adverse effects on lung function or altered bone mass in early school-age children [47,48].…”
Section: Multiple Steroid Dosesmentioning
confidence: 90%
“…Since the trials conducted by Liggins and Howie in 19726), many observational and controlled studies have reported that antenatal administration of glucocorticoids (GCs) to mothers at risk of preterm birth decreases the severity of respiratory distress syndrome and improves the survival of preterm infants6,7,8,9,10). However, repeated courses of antenatal GCs may be associated with reduced fetal brain growth and long-term neurodevelopmental impairment10,11,12,13,14,15,16,17). Several studies of systematic reviews and meta-analyses have shown that postnatal use of GCs to prevent or treat chronic lung disease (CLD) in preterm infants may facilitate extubation and decrease the incidence of bronchopulmonary dysplasia (BPD), but have found that it increases the risk of neurodevelopmental impairment and cerebral palsy (CP), particularly in infants treated with dexamethasone within the first week of life2,3,4,5,18,19,20,21,22,23,24).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, corticosteroids decrease the longitudinal growth. Previous studies have shown that there is a correlation between the number of doses and amount of steroid given antenatal and during neonatal period [1,2]. After the end of repeated administration of antenatal corticosteroids there was a postnatal growth acceleration, catch up, 3-5 weeks after birth [1].…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies have shown that there is a correlation between the number of doses and amount of steroid given antenatal and during neonatal period [1,2]. After the end of repeated administration of antenatal corticosteroids there was a postnatal growth acceleration, catch up, 3-5 weeks after birth [1]. Keller et al have found that short-term growth of premature infants treated with dexamethasone for BPD, was decreased for up to 72 hours after stopping therapy [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation